2006
DOI: 10.1145/1118178.1118182
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation support

Abstract: A plethora of technologies exist that are not necessarily tools. For technologies to become a tool, we contend, argumentation routines and design must coevolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The Engagement Features architecture facilitates engagement once users have agreed on the rules for interaction. The features stem from the engagement literature (Johnston & Taylor, 2018) and work by Aakhus (Aakhus, 2011;de Moor & Aakhus, 2006) on ways to construct deliberation through structured interaction. Aakhus (2011) has suggested that there are ways to structure argumentation through technologies.…”
Section: Reimagining Dialogic Social Media As Spaces For Social Discumentioning
confidence: 99%
“…The Engagement Features architecture facilitates engagement once users have agreed on the rules for interaction. The features stem from the engagement literature (Johnston & Taylor, 2018) and work by Aakhus (Aakhus, 2011;de Moor & Aakhus, 2006) on ways to construct deliberation through structured interaction. Aakhus (2011) has suggested that there are ways to structure argumentation through technologies.…”
Section: Reimagining Dialogic Social Media As Spaces For Social Discumentioning
confidence: 99%
“…In system side, secondly, Ramesh and Whinston (1994) argued that group argumentation process in decision support system (DSS) consists of three formalisms as representation, gaming, and coordination, meanwhile proposed a framework of argumentative reasoning facilitation systems (ARFS). De Moor and Aakhus (2006) extended traditional IS modeling approaches for a Language-action Perspective (LAP), and developed a LAP-based diagnostic method to support argumentation. Vetschera (2007) examined the preferences embedded in electronic negotiation support systems for exactly reflecting the behavior of negotiators and negotiation outcomes, with an empirical manner.…”
Section: Group Argumentationmentioning
confidence: 99%
“…It has been also admitted that these solutions often require that users carry out activities that do not naturally belong to their work, or they support activities which are infrequent in normal work; thus, such activities are often considered artificial or insignificant by users. As a result, traditional argumentation software approaches are no longer sufficient to support contemporary communication and collaboration needs (de Moor & Aakhus, 2006). There is a need to provide alternative representational features to demonstrate a significant effect on the users' collaborative knowledge building process.…”
Section: Existing Approachesmentioning
confidence: 99%